LITERATURE REVIEW: STRATEGI MENINGKATKAN KETERAMPILAN MEMBACA SISWA SEKOLAH DASAR - Juliati; Ain, Imelja Nurul; Khairalayali; Juliani, Melly; Dalimunte, Sofy Delfiana; Juliana, Sri; Sembiring, Satria Doni (Universitas Negeri Medan, 2025)
The purpose of this study is to examine scientific articles on strategies to enhance elementary school pupils' reading comprehension abilities using the literature review method. The literature discussed are papers released within the previous five years. (2021-2025) with the keyword “reading skills”, which were retrieved from Google Scholar. Of the 144,000 articles identified throughout elementary, middle, and high school, sorting was done based on research topics. The analysis showed that the Think, Predict, Read, Connect (TPRC) strategy is the most effective in improving reading skills because it involves critical thinking, prediction, direct reading, and linking the text with personal knowledge, so that students not only read mechanically but also understand the content.